Penguatan Pemasaran Dan Branding Produk Telur Asin Di Desa Baha Kecamatan Mengwi Kabupaten Badung - i Made Pulawan; Dewa Ayu Niti Widari; A.A. Avu ErnaTrisnadewi (Jurnal Pengabdian Masyarakat Akademisi, 2023)
Abstract The MSME sector is expected to be able to become a new source of strength for the national economy in facing the crisis. To become a new force in the economic sector, the government should pay attention to human resources and management. It is felt that innovation from the average MSME is still minimal so that MSME businesses often run in place. One of the villages targeted for PKM activities is the salted egg business group in Baha Village, Mengwi-Badung District. The problem faced by partners is that it is difficult to develop the business. These include lack of promotion, not yet using online marketing, and not keeping bookkeeping records related to costs incurred. has been issued and in running the business the partner runs the business in a family manner. The results of the service show an increase in partners' understanding regarding good financial management, calculating the cost of goods sold in an effort to optimize profits that will be generated and the use of social media in business promotion, because this will have an impact on business sustainability.